Building sustainable peace through an integrated approach to peacebuilding and mental health and psychosocial support: a literature review. Issue 3 (November 2017) - Tankink, Marian; Bubenzer, Friederike
Abstract : N/A: The contribution of the fields of mental health and psychosocial support and peacebuilding is critical to the repair of societies affected by war and violent conflict. Despite some advances in bringing the two fields closer together, the evidence base for the outcomes and impact of an integrated approach included both mental health and psychosocial support and peacebuilding is still very thin. The hypothesis for this literature review was that a combined approach would enhance the knowledge base and, therefore, foster the prospect of sustainable peace. The literature reviewed indicates that while there is an increasing awareness of the need to bring some of the knowledge and tools traditionally belonging to the field of mental health and psychosocial support into peacebuilding interventions (and vice versa), this is not yet practiced in a way that is fully integrated from the outset or is holistic on a systemic level. This study highlights the need for the development of a theoretical model that bridges both fields as a foundation for future research and practice.